The Role of Experiential Marketing in Enhancing Customer Loyalty in the Digital Era: An Applied Study on Iraqi E-Commerce Platforms - Hussein , Ridha Naeem (American Journal of Economics and Business Management, 2024)
This study seeks to: understand the nature of customer interaction with marketing experiences and the impact of these experiences on customer loyalty towards the platform. The study is on e-commerce platforms in Iraq, which are chosen based on their activity and importance. The sample was selected in the Tamata and Miswaq platforms, and the targeted sample included 200 active customers working on using e-managing platforms in Iraq. This study adopted the mixed method of both qualitative and quantitative. The data was collected using questionnaires that were administered to a sample of customers who used Iraqi e-commerce platforms. The data represented that customers identified positively with the dissimilarity in marketing experience and this shows marketing experientialism positively contributes to customer loyalty. The researcher suggested that Iraqi electronic commerce sites should start investing.